# Proof

(related to Theorem: Quadratic Reciprocity Law)

• By hypothesis, $p > 2$ and $q > 2$ are odd and distinct prime numbers.
• If $q\ge 2,$ then we can set according to division with quotient and remainder for $1\le k\le \frac{p-1}2$ $$\label{eq:E18755a}\tag{1}kq=q_kp+r_k,\quad 0 < r_k < p.$$ Note that $r_k\neq 0,$ since $q$ and $p$ are distinct.
• Moreover, we have $q_k=\left\lfloor\frac{kq}p\right\rfloor$ due to the connection between quotient, remainder, modulo and floor function.
• In the proof of the Gaussian lemma, we have seen (with the same notation as there) that the remainders $a_s$, $p-b_t$ the same numbers as the numbers $$1,2,\ldots,\frac{p-1}2,$$ apart from the order.
• Therefore, with $a:=\sum_{s=1}^l a_s$ and $b:=\sum_{t=1}^m b_t$, we have the sum $$\sum_{k=1}^{\frac{p-1}2}r_k=a+b.$$
• On the other hand, the sum of arithmetic progression gives us $$\label{eq:E18755b}\tag{2}\frac{p^2-1}8=\frac{\frac{p-1}{2}\cdot \frac{p+1}{2}}{2}=\sum_{k=1}^{\frac{p-1}{2}}k=a+mp-b.$$
• Adding the equations $(\ref{eq:E18755a}),$ we get $$\label{eq:E18755c}\tag{3}\frac{p^2-1}8q=p\sum_{k=1}^{\frac{p-1}{2}}q_k+\sum_{k=1}^{\frac{p-1}{2}}r_k=p\sum_{k=1}^{\frac{p-1}{2}}q_k+a+b.$$
• From $(\ref{eq:E18755b})$ and $(\ref{eq:E18755c}),$ we get $$\frac{p^2-1}8(q-1)=p\sum_{k=1}^{\frac{p-1}{2}}q_k-mp+2b,$$ and the congruence. $$\label{eq:E18755d}\tag{4}\frac{p^2-1}8(q-1)\equiv \sum_{k=1}^{\frac{p-1}{2}}q_k+m\mod 2.$$
• For $q=2$, all $q_k=0,$ and we have $\frac{p^2-1}8\equiv m\mod 2$ and therefore according to the Gaussian lemma, the formula for the Legendre symbol. $$\left(\frac 2p\right)=(-1)^m=(-1)^{\frac{p^2-1}8}.$$
• Let $q > 2.$ Then $q-1$ is even, and we have in $(\ref{eq:E18755d})$ $$\sum_{k=1}^{\frac{p-1}{2}}q_k\equiv m\mod 2.$$
• Therefore, applying the Gaussian lemma once again, we get the formula $$\label{eq:E18755e}\tag{5}\left(\frac qp\right)=(-1)^m=(-1)^{\sum_{k=1}^{\frac{p-1}{2}}\left\lfloor\frac{kq}p\right\rfloor}.$$
• From symmetry reasons, the same holds for $$\label{eq:E18755f}\tag{6}\left(\frac pq\right)=(-1)^{\sum_{l=1}^{\frac{q-1}{2}}\left\lfloor\frac{lp}q\right\rfloor}.$$
• $(\ref{eq:E18755e})$ and $(\ref{eq:E18755f})$ give us together the result $$\left(\frac qp\right)\cdot \left(\frac pq\right)=(-1)^{\alpha}$$ with $$\alpha=\sum_{k=1}^{\frac{p-1}{2}}\left\lfloor\frac{kq}p\right\rfloor+\sum_{l=1}^{\frac{q-1}{2}}\left\lfloor\frac{lp}q\right\rfloor.$$
• It remains to be shown that $$\alpha=\frac{p-1}{2}\cdot\frac{q-1}{2},$$ but this follows from the reciprocity law for floor functions.

Thank you to the contributors under CC BY-SA 4.0!

Github:

### References

#### Bibliography

1. Landau, Edmund: "Vorlesungen über Zahlentheorie, Aus der Elementaren Zahlentheorie", S. Hirzel, Leipzig, 1927